The intimate frontier : friendship and civil society in northern New Spain - Martínez, Ignacio (University and college faculty member) (The University of Arizona Press, 2019)
"Building on the most recent scholarship in borderlands history, The Intimate Frontier is an intellectual and social history that explores the immensely complex web of interpersonal relationships and layers of emotional sophistication inherent among frontier communities"--